A new species of Cyrtodactylus Gray, 1827 (Squamata, Gekkonidae) from Yunnan Nangunhe National Nature Reserve, China - Shuo Liu; Zhimin Li; Wenguang Duan; Mian Hou; Dingqi Rao (ZooKeys)
A new forest-dwelling species of the Cyrtodactylus chauquangensis group is described from southwestern Yunnan Province, China. Phylogenetically, it was recovered as the sister species of C. zhenkangensis, with a genetic distance of 9.2% in the ND2 gene. Morphologically, the new species can be separated from C. zhenkangensis by the discontinuity of enlarged femoral scales and enlarged precloacal scales, the absence of femoral pores, and the difference in dorsal color pattern. In addition, although the new species and C. zhenkangensis are distributed relatively close, their habitats are clearly different. Cyrtodactylus zhenkangensis inhabits karst limestone, while the new species inhabits forest. The new species is the 29th species of the C. chauquangensis group and the third forest-dwelling species of this group.